FAKTOR FAKTOR YANG MEMPENGARUHI DEBT POLICY PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Anson Ivanditantra; Viriany Viriany (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this research is to analyze the impact of profitability, asset structure, liquidity, managerial ownership and firm size on debt policy. This research is conducted bu using 162 samples of manufacturing companies listed in Indonesia Stock Exchange during 2017-2019, using purposive sampling method and processed using EViews 11 student version. The result of partially test ( t test) shows that profitability and firm size has significant effect on debt policy, while asset structure, liquidity and managerial ownership have no significant effect on debt policy.